2004
DOI: 10.1097/01.alc.0000108654.77178.03
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Hepatic Methionine and Glutathione Metabolism in Patients With Alcoholic Hepatitis

Abstract: In alcoholic hepatitis, abnormal hepatic gene expression in methionine and GSH metabolism occurs and often contributes to decreased hepatic methionine, S-adenosylmethionine, cysteine, and GSH levels. It may be important to replenish these thiols in patients hospitalized with alcoholic hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 43 publications
9
98
1
2
Order By: Relevance
“…These observations are consistent with the study by Lieber et al showing that alcohol consumption decreased hepatic phosphatidylethanolamine N-methyltransferase activity in a baboon model of alcohol-induced hepatic fibrosis [14]. Furthermore, a recent study by Lu's group documented decreased mRNA for multiple methyltransferases in liver biopsies from patients with alcoholic hepatitis [15]. More importantly, our recent studies have shown for the first time that elevation of intracellular SAH levels can sensitize to TNF hepatotoxicity [12]; however, the mechanism for this is still not fully understood.…”
Section: Introductionsupporting
confidence: 90%
“…These observations are consistent with the study by Lieber et al showing that alcohol consumption decreased hepatic phosphatidylethanolamine N-methyltransferase activity in a baboon model of alcohol-induced hepatic fibrosis [14]. Furthermore, a recent study by Lu's group documented decreased mRNA for multiple methyltransferases in liver biopsies from patients with alcoholic hepatitis [15]. More importantly, our recent studies have shown for the first time that elevation of intracellular SAH levels can sensitize to TNF hepatotoxicity [12]; however, the mechanism for this is still not fully understood.…”
Section: Introductionsupporting
confidence: 90%
“…30,31 Human HepG2 cells that overexpress CYP2E1 have been shown to have elevated glutathione levels for protection against oxidative stress, 32 and a recent study in patients with alcohol-associated hepatitis has shown that both glutathione and CYP2E1 messenger RNA were reduced by 70%-80%. 33 The effect of APAP on the level of glutathione is of importance in the context of this study, because the lipoyl domain of PDC-E2 is modified by glutathionylation during apoptosis with this modification blocking PDC-E2 recognition by AMAs. 12 This phenomenon is significant in PBC, because biliary epithelial cells do not glutathionylate PDC-E2 during apoptosis, whereas other liver cells do.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with alcoholic liver disease are known to have low hepatic and plasma GSH levels (Vendemiale et al, 1989;Tsukamoto and Lu 2001;Lee et al, 2004). The reason for this is multi-factorial.…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%